(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Even in areas where modernized medicine isavailable, plant-derived substances and natural medicines have currently attracted super interest towards their flexible application, due to the reachest source of bioactive compounds. Herbal products are not only the most effective, but they are fantastically non-poisonous and have therapeutic doses properly underneath their toxic levels. Ointments are topical formulations that provide higher patient compliance and hence turn out to be more suited.due to the presence of antioxidants and anti-inflammatory components.of Curcuma longamay provide glow and luster to the skin andmay also revive skin by bringing out its natural glow.comparably,Piper nigrumhasantibacterial and anti-inflammatory properties that help cure skin infections and acne. Ointment formulation was prepared using an oily base by the trituration method. Further, the formulation was prepared with 0.6gm Curcuma longa extract and 0.2gm of piper nigrumextract.The physicochemical properties were studied which showed satisfactory results for spreadability, extrudability, washability, solubility, loss on drying, and others. Also, the formulation was placed for a stability study at different temperature conditions like 2°C, 25°C, and 37°C for four weeks. No changes were observed in spreading ability, diffusion study as well as irritant effect. Thus, an ointment formulation containing Curcuma longa and piper nigrum extract could become a medium to use the medicinal properties of these herbs effectively.